Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173956
|View full text |Cite
|
Sign up to set email alerts
|

ThermoKiosk

Abstract: Thermal comfort in shared workplaces is often contested and impacts productivity, wellbeing, and energy use. Yet, subjective and situated comfort experiences are rarely captured and engaged with. In this paper, we explore roles for digital surveys in capturing and visualising subjective experiences of comfort in situ for comfort management. We present findings from a 3-week field trial of our prototype system called ThermoKiosk, which we deployed in an open plan, shared office with a history of thermal comfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…There is potential to use data and technology to create flexible spaces, to give more control instead of less: The Janus Face of Smart Building Data hints at how this might be enacted through transparency and involvement of occupants in conversations. Thermal comfort has been extensively examined from this perspective [17], and it is well recognised that an increased locus of control is psychologically beneficial to feelings of comfort [29]. Comfort is not the only factor determining the fitness for purpose of a building, though, and it appears that designing for perception of control holistically could be approached as a starting point in improving occupant agency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is potential to use data and technology to create flexible spaces, to give more control instead of less: The Janus Face of Smart Building Data hints at how this might be enacted through transparency and involvement of occupants in conversations. Thermal comfort has been extensively examined from this perspective [17], and it is well recognised that an increased locus of control is psychologically beneficial to feelings of comfort [29]. Comfort is not the only factor determining the fitness for purpose of a building, though, and it appears that designing for perception of control holistically could be approached as a starting point in improving occupant agency.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there is surprisingly little cross-over or engagement within HBI with HCI work which addresses hegemony or power imbalances [36], or feminist notions of agency, equity and empowerment [4]. Clear et al [16,17] focus on occupant participation in building evaluation and management. They investigate the role of environmental data as a mechanism to mediate interactions between building managers and occupants, and suggest ways that it can leveraged for more inclusive and bottom-up building management [16].…”
Section: Related Literature Hci and Building Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional models found in literature such as surveys are insufficient as their sampling rates are low, require the occupant to completely stop their task at hand to focus on the survey, and in many cases, ask for a recollection of past experiences. There is the further issue of survey fatigue [63] and even when willing to participate, there is a concern about how accurate their responses are [66]. The use of a smartwatch for data collection, coined micro ecological momentary assessments, is so user-friendly that it does not significantly disrupt any ongoing activity [52].…”
Section: Ecological Momentary Assessments (Ema)mentioning
confidence: 99%
“…• Longitudinal studies are not able to look at the micro-climates found within office environments. Hot and cold spots are known to be sources of tension [1], and issues surrounding ownership of windows and radiators [8] compound this further. By not considering these localised effects, our buildings are actively working against the social dynamics causing discomfort.…”
Section: A Third Approachmentioning
confidence: 99%